Evaluation and detoxification of aflatoxins in ground and tree nuts using food grade organic acids. (October 2020) - Jubeen, Farhat; Sher, Farooq; Hazafa, Abu; Zafar, Fatima; Ameen, Mariam; Rasheed, Tahir
Abstract: The contamination of foodstuffs especially nuts with aflatoxins (AFs) affected by some of the fungal genera species is a major threat to the economy, safe food supply and serious health concerns to any country in recent days. Recently different techniques including heat, ozone and microbes are used for the decontamination of aflatoxin but all these are limited to achieve the desirable results. The present study objectives to decontaminate AFs in nuts by using three food-grade organic acids. The aqueous solutions of three food-grade organic acids namely citric, lactic and propionic acid are used at five different concentrations (1, 3, 5, 7 and 9%) to detoxify aflatoxin B1 (AFB1 ) and total aflatoxins (TAFs) that includes ;AFB1, AFB2, AFG1 and AFG2 in selected nuts including almond, peanut, pistachio and walnut at two different moisture levels (10 ± 3 and 16 ± 3%). The high-performance liquid chromatography (HPLC) coupled with fluorescence detection method was applied for the qualitative and quantitative determination of AFs. The results showed that the decontamination of AFB1 and TAFs significantly increased in infected nuts by increasing the concentration of acids. The experimental results after 15 min treatment of walnut (10 ± 3 and 16 ± 3% moisture level), pistachio (10 ± 3% moisture content) and peanuts (10 ± 3% moisture content) with citric, lactic and propionic acids at 9% concentration significantly reduced AFs about 99, 99.90 and 96.07% respectively. Furthermore, treatment with citric and lactic acids resulted in the conversion of AFB1 into less toxic products identified as AFD1 via hydrolysis of the lactone ring. Furthermore, citric acid was found as the most efficient acid in degrading the TAFs among all three organic acids. The present study showed better AFs detoxification results than conventional methods. Hence, it is concluded that citric, lactic, and propionic acids can be applied as a useful and safe decontamination method for AFB1 and TAFs in aflatoxin-affected nuts. Graphical abstract: Image 1 Highlights: Detoxification of AFB1 and TAFs is investigated in nuts by three food grade organic acids. Citric acid significantly detoxified AFB1 and total AFs in the selected nuts. Lactic acid effectively converted the toxic AFB1 into less hazardous product AFB2 . Propionic acid was found as a prominent acid for degradation of AFB1 in walnuts. Citric, lactic and propionic acids could be a viable option for the reduction of AFB1 and TAFs in nuts.